Preharvest Hydrogen Peroxide Treatment Delays Leaf Senescence of Chinese Flowering Cabbage During Storage by Reducing Water Loss and Activating Antioxidant Defense System - Wang, Guang; Peng, Miaomiao; Wang, Yanjing; Chen, Zhuosheng; Zhu, Shijiang (Frontiers in Plant Science, 2022)
Leaf yellowing, an indicator of senescence, reduces commercial value of Chinese flowering cabbage after harvest. Hydrogen peroxide (H2O2) plays a dual role in mediating plant stress responses, but it is not clear whether and how it affects leaf senescence when exogenously stimulating the plants before harvest. Here, we found that preharvest application with low concentrations of H2O2 to root delays leaf senescence. Around 10 mM H2O2 reduced leaf yellowing rate by 8.2 and 26.4% relative to the control following 4 and 8 days storage, respectively. The H2O2-treated cabbages showed higher chlorophyll and lower relative expression of senescence-associated gene (SAG) BrSAG12 than the control. Proteomic analysis revealed 118 and 204 differentially expressed proteins (DEPs) in H2O2-treated plants at 4 and 8 days of storage, respectively. The main DEPs are involved in chlorophyll degradation and synthesis, water deprivation, antioxidant activity, and protections on chloroplast membranes. Decline of water loss in H2O2-treated cabbages was coincide with increase of proline contents and modulation of leaf stomatal aperture. Alleviation of oxidative stress was indicated by suppression of respiratory burst oxidase homolog and upregulation of reactive oxygen species (ROS) scavenging-related genes. These results were also supported by the alleviation of lipid peroxidation and the protections on cell integrity and photochemical efficiency in H2O2-treated group. Collectively, preharvest H2O2 treatment alleviates water loss and activates antioxidant defense system, protects chloroplast membrane from oxidative damage, and ultimately delays leaf senescence during storage. This study provides novel insights into the roles of H2O2 for regulating leaf senescence of Chinese flowering cabbage.